2016
DOI: 10.1016/j.joca.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structural pathology and pain behaviour in a model of osteoarthritis (OA)

Abstract: SummaryObjectivesTo address the hypothesis that different types of established osteoarthritis (OA) pain behaviours have associations with different aspects of articular pathology, we investigated the relationship between structural knee joint pathology and pain behaviour following injection of a low vs a high dose of monosodium iodoacetate (MIA) in the rat.MethodsRats received a single intra-articular injection of 0.1 mg or 1 mg MIA or saline (control). Pain behaviour (hind limb weight bearing asymmetry (WB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…Despite these behavioural observations, knee joint pathology in the form of degradation of articular cartilage accompanied by inflammation in the synovial membrane was exhibited by both the TASTPM and WT mice 4 weeks post‐MIA administration. Intra‐articular administration of MIA has been shown to display mechanical hypersensitivity in the absence of weight bearing deficits in a dose‐dependent manner, despite the knee joint pathologies (Ogbonna et al., ; Nwosu et al., ). Therefore, mechanical hypersensitivity and absence of ongoing pain exhibited by the transgenic model of AD may suggest a possible alteration of central plasticity mechanisms of MIA‐induced OA pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these behavioural observations, knee joint pathology in the form of degradation of articular cartilage accompanied by inflammation in the synovial membrane was exhibited by both the TASTPM and WT mice 4 weeks post‐MIA administration. Intra‐articular administration of MIA has been shown to display mechanical hypersensitivity in the absence of weight bearing deficits in a dose‐dependent manner, despite the knee joint pathologies (Ogbonna et al., ; Nwosu et al., ). Therefore, mechanical hypersensitivity and absence of ongoing pain exhibited by the transgenic model of AD may suggest a possible alteration of central plasticity mechanisms of MIA‐induced OA pain.…”
Section: Discussionmentioning
confidence: 99%
“…The development of experimental models for OA is of fundamental importance for the understanding of the pathophysiology of the pathology, for example, through experimental models in rats as shown in Figure 3; it was possible to observe a much more complex relation between the histological morphology of the cartilaginous tissue and the pain phenotypes. It can contribute significantly in understanding the mechanisms of cellular development and interaction in diseased joints as well as in the targeting of patients' analgesic therapy [21].…”
Section: Cartilage Lesionsmentioning
confidence: 99%
“…Similar assessments have been frequently made in chemical models of osteoarthritis such as those induced by intra-articular monoiodoacetate (MIA) injection; however, the disease progression in these models develops far more rapidly than surgical models [68 ▪▪ ]. A recent study examining pain-related behaviors in rats with bilateral intra-articular injection of MIA demonstrated that decreased spontaneous animal burrowing is correlated with spontaneous animal activity and rearing indicative of pain [69 ▪▪ ].…”
Section: Pain Assessment and Nerve Growth Factormentioning
confidence: 99%